2002
DOI: 10.1292/jvms.64.987
|View full text |Cite
|
Sign up to set email alerts
|

Production of Conjugated Linoleic Acid by Intestinal Bacteria in Dogs and Cats.

Abstract: ABSTRACT. Production of conjugated linoleic acid (CLA) by the intestinal bacteria of dogs and cats was demonstrated by incubating their feces with linoleic acid (LA). CLA accumulated once, and then decreased with time. The numbers of LA-hydrogenating bacteria in the intestines appeared to decrease greatly with the ages of dogs and cats. As a major product of LA biohydrogenation, trans-vaccenic acid (t-VA) was identified. Most CLA and t-VA were readily solubilized by shaking the incubation mixture with bovine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 32 publications
(31 reference statements)
2
26
0
1
Order By: Relevance
“…B. fibrisolvens also resides in the intestines of humans (Wedekind et al, 1988), dogs (Asanuma et al, 2001), and cats (Asanuma et al, 2001). We showed that CLA is produced by the mixed bacteria harvested from dog and cat feces (Fukuda et al, 2002b). Introduction of B. fibrisolvens as a probiotic may enhance CLA supply, and contribute to the health of these animals.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…B. fibrisolvens also resides in the intestines of humans (Wedekind et al, 1988), dogs (Asanuma et al, 2001), and cats (Asanuma et al, 2001). We showed that CLA is produced by the mixed bacteria harvested from dog and cat feces (Fukuda et al, 2002b). Introduction of B. fibrisolvens as a probiotic may enhance CLA supply, and contribute to the health of these animals.…”
mentioning
confidence: 58%
“…Cultures were routinely incubated in triplicate at 39°C, maintaining the pH between 6.5 and 7.0 (Miyazaki et al, 1992). Details of culture conditions and procedures were as described previously (Fukuda et al, 2002a). Cell growth was estimated by measuring the optical density at 600 nm (OD 600 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations